A relationship-based approach for energy aware secure routing in MANETs. (2016) - Rathnamma, M.V.; Reddy, P. Chenna
Secure routing is one of the major issues which is affecting the widespread use of MANETs. To address this issue several methodologies have been proposed and some of them were able to achieve a considerable amount of success but with a considerable amount of computational overhead. In this paper, we propose a new secure routing mechanism for MANETS. This mechanism uses trust-based method to establish secure routes. It is a family relationship-based approach in which security is established by considering certain parameters which can be used to determine the ingenuity of the nodes. It also considers the parameters like energy consumption and signal strength of the node. The proposed method does not use any protocol specific parameter and thus can be used over any on demand routing protocol like AODV or DSR. As components of MANETs have several resource constraints, this paper aims at providing an improved AODV protocol called secure family-based routing protocol (SFRP) with reduced resource consumption and security enabled.